2021
DOI: 10.1002/alz.12438
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment associated with greater care intensity during home health care

Abstract: Background:In Medicare-funded home health care (HHC), one in three patients has cognitive impairment (CI), but little is known about the care intensity they receive in this setting. Recent HHC reimbursement changes fail to adjust for patient CI, potentially creating a financial disincentive to caring for these individuals.Methods: This cohort study included a nationally representative sample of 1214 Medicare HHC patients between 2011 and 2016. Multivariable logistic and negative binomial regressions modelled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…This echoes research demonstrating an association between cognitive impairment and greater care needs in other care settings 3–6,8 . While there is limited information specific to home health, prior work indicates that patients with cognitive impairment receive a greater number of visits 17 over a longer period of time, 16 and that receiving more visits lowers the risk of unplanned readmission and institutionalization for these patients 45 . Given this link between care intensity and outcomes, it is concerning that CMS reported a decline in the average number of home health visits provided following the recent payment system revision 34…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This echoes research demonstrating an association between cognitive impairment and greater care needs in other care settings 3–6,8 . While there is limited information specific to home health, prior work indicates that patients with cognitive impairment receive a greater number of visits 17 over a longer period of time, 16 and that receiving more visits lowers the risk of unplanned readmission and institutionalization for these patients 45 . Given this link between care intensity and outcomes, it is concerning that CMS reported a decline in the average number of home health visits provided following the recent payment system revision 34…”
Section: Discussionmentioning
confidence: 72%
“…Prior work finds that M1700 has strong inter‐rater reliability 27 and gold‐standard validity 28 . As in previous literature, 17 we categorized those rated “0” on the 5‐item scale as having no identified cognitive impairment and all others as having identified cognitive impairment. (See Appendix Section A of Supporting information for additional detail on this measure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 60 days, recovery decreased, possibly reflecting continued high care needs. A 2022 study 40 among recipients of HHC with cognitive impairment found a high intensity of HHC needs. This is particularly important given that the recently implemented case-mix classification model for HHC reimbursement, the Patient-Driven Groupings Model (PDGM), relies heavily on acute clinical characteristics and does not account for pre-existing vulnerabilities, such as cognitive impairment or frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cognitive impairment were identified based on clinician assessment of cognitive impairment, captured in an OASIS item on cognitive functioning (M1700). As described previously by Burgdorf et al, 22 responses rated “0” on the 5-item scale reflective of being “alert/oriented, able to focus and shift attention, comprehends and recalls task directions independently” were categorized as having no identified cognitive impairment, whereas responses of “1,” “2,” “3,” or “4” were indicative of cognitive impairment 22 . Starting with HHC episodes beginning between December 2016 and December 2017 (n = 824 075), we excluded beneficiaries younger than 65 years and those without ADRD or cognitive impairment (N = 250 032 [30.3%]).…”
Section: Methodsmentioning
confidence: 99%